2018
DOI: 10.21037/jtd.2018.08.93
|View full text |Cite
|
Sign up to set email alerts
|

Lung volume reduction surgery beyond the NETT selection criteria

Abstract: Lung volume reduction surgery (LVRS) for symptomatic patients with advanced emphysema was proven to be successful in a large randomized multi-center trial (NETT) and in several smaller randomized single center trials. This evidence primarily concerns patients with heterogeneous, upper-lobe predominant emphysema and low exercise tolerance within certain selection criteria regarding lung function values. As the most important effect of LVRS is generated by reducing the hyperinflation, even patients with homogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Although improvement of lung function and exercise capacity are achieved, durability of these beneficial effect is shorts in patients with AATD is shorter compared with patients without AATD after LVRS. Similar results were reported by the Zurich group (23) and are also discussed elsewhere in this issue.…”
Section: Indications For Lvrssupporting
confidence: 91%
See 2 more Smart Citations
“…Although improvement of lung function and exercise capacity are achieved, durability of these beneficial effect is shorts in patients with AATD is shorter compared with patients without AATD after LVRS. Similar results were reported by the Zurich group (23) and are also discussed elsewhere in this issue.…”
Section: Indications For Lvrssupporting
confidence: 91%
“…Weder et al reported long-lasting and significant improvement of lung function and reduction of dyspnea measured by the medical research council dyspnea score (MRCDS) in 138 patients with homogenous emphysema (22). The crucial criteria in selecting these patients for LVRS is severe hyperinflation with a residual volume to total lung capacity ratio (RV/TLC) greater than 60% and FEV-1% and DLCO% both above 20% predicted (23).…”
Section: Indications For Lvrsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the obvious upper-lobe-predominant type of emphysema gives few problems in identifying the target area (figures 1-4), the identification of possible targets in other locations is much more challenging. As we have demonstrated for many years that well-selected patients with intermediate heterogeneous and even homogenous emphysema can also profit from LVRS [2,17] the correct assessment of morphology is essential and improved using 3D imaging. The example in figure 5 shows a relevant target zone in the upper part of the left lower lobe, which is well visible on 3D imaging and densitometry and further confirmed intra-operatively.…”
Section: Discussionmentioning
confidence: 99%
“…Lung volume reduction surgery (LVRS) is intended to remodel hyperinflated lungs to normal size by resecting the most functionless parts of the emphysematous lung in symptomatic patients with COPD [1,2]. Volume reduction results primarily in improved respiratory mechanics and hence to a decrease in dyspnoea, an improvement of lung function and an increase of quality of life [3,4].…”
Section: Introductionmentioning
confidence: 99%